Pengolahan Produk Pangan Berbasis Ketela dan Minuman Sehat Fermentasi Sebagai Langkah Meningkatkan Nilai Produk Lokal di Desa Seloliman, Kecamatan Trawas, Kabupaten Mojokerto - Johan Sukweenadhi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
AbstractÂ Cassava and sweet potato are the main commodity plants in Seloliman. So far, the farmer there directly sell it after harvesting process. However, in case the sales are not much and many quantities of cassava or sweet potato remains, it become tainted which can reduce its quality or ever become waste. Less of knowledge about post harvesting process of that plant makes people less concerned about the potential of its processed product. With the knowledge sharing and workshop of cassava and sweet potato post harvesting process, the society will have insight and knowledge how to process their excess cassava become more valuable food products. Other utilization of healthy fermented drink from microbe symbiont like kefir and kombucha, which use the local flowers or fruits, can be done to boost the local beverage products in Seloliman. Both ways can be one of the steps to empower the Seloliman society to brand their unique products in the future.Keywords: cassava, post-harvest, healthy fermented drink, kefir, kombucha